GERAKAN MENUJU SEKOLAH HIJAU BERWAWASAN KONSERVASI DI SD PELEBURAN 03 DAN SD PELEBURAN O4 SEMARANG - Marianti, Aditya; Saptono, Sigit; Abdullah, Muhammad (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2018)
Land shortage becomes the main environmental problem for many schools in urban areas. Hygienic and eco-friendly behavior, along with waste management are not optimally conducted in the schools. This problem is also encountered in SD Pleburan 03 and SD Pleburan 04, Semarang, Indonesia. This program aims to raise environmental awareness of people in the school to take part in embodying the green school program. The responsibility also belongs to UNNES as one of the conservation-centered universities. Therefore, UNNES community empowerment team carried out a community empowerment program to actualize the environmentally-centered green school idea in SD Pleburan 03-04. Methods applied were arranged in various stages of activities, which are socialization, integration, implementation, monitoring, and evaluation. Results show that the principal and the teachers of the school are able to develop environmentally based learning infrastructures. Teachers are also able to practice environmentally based learning process. Students are capable to practice hydroponic techniques. Moreover, the school now also possesses an eco –friendly supporting system. In conclusion, this program encourages people of SD Pleburan 03-04 to move forward as an environmentally based green school.